A cement adhesive and its preparation method and application
By adding gas induction agent and high-efficiency polycarboxylic acid water reducing agent to the cement adhesive and limiting the water-cement ratio range, the problem of poor cold resistance in high-cold areas is solved, and good adhesion and durability under extremely low temperature conditions are achieved.
Patent Information
- Application Number
- CN202411569803.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The existing cement adhesives have poor cold resistance in high-altitude areas and are prone to cracking, failure or degradation due to temperature changes.
An improved cement adhesive was prepared by adding gas induction agents, limiting the water-cement ratio range, and combining aluminate cement, artificial porcelain sand, titanium oxide, silicon micropowder and high-efficiency polycarboxylic acid water reducing agents. The bubbles formed by the gas induction agent can absorb freezing stress, prevent moisture from penetration, and absorb shrinking stress during drying, thereby improving cold resistance.
It significantly improves the cold resistance of cement adhesives, ensuring that good adhesion and durability can be maintained under extremely low temperature conditions, and avoids cracking, failure or degradation.
Smart Images

Figure CN119059783B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cement adhesives, and in particular relates to a cement adhesive and a preparation method and application thereof. Background Art
[0002] In high-cold areas, extremely low temperatures may have an adverse effect on the performance of cement adhesives for porcelain insulators. Improving the quality of cement adhesives can enhance their cold resistance and ensure good adhesion and durability under extremely low temperature conditions. This can prevent cracking, failure or degradation of the adhesive caused by temperature changes, thereby ensuring the normal operation and reliability of the insulator.
[0003] The components of current cement adhesives are mainly aluminate cement, artificial porcelain sand, halloysite, titanium oxide and admixtures, but their cold resistance is poor. When used in high-cold areas, the cement adhesive will crack or peel due to temperature changes. Therefore, how to improve the cement adhesive to improve its cold resistance has become a technical problem that needs to be solved urgently in this field. Summary of the invention
[0004] The purpose of the present invention is to provide a cement adhesive and a preparation method and application thereof. The cement adhesive provided by the present invention can improve the cold resistance of the cement adhesive.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a cement adhesive, comprising the following components: aluminate cement, artificial porcelain sand, titanium oxide, silica powder, external admixture and water;
[0007] The water-cement ratio of the cement adhesive is 0.1-0.2;
[0008] The external admixtures include air entraining agent, water reducing agent, antifreeze agent, reinforcing agent and steep wave performance improving agent;
[0009] The water reducer is a high-efficiency polycarboxylate water reducer;
[0010] The mass of the reinforcing agent is 0.1-0.3% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silicon powder.
[0011] Preferably, the mass of the aluminate cement is 45-60% of the total mass of the aluminate cement, artificial porcelain sand, titanium oxide and silica powder.
[0012] Preferably, the mass of the artificial porcelain sand is 35-50% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder.
[0013] Preferably, the mass of the titanium oxide is 1-3% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder.
[0014] Preferably, the particle size of the titanium oxide is 20-80 nm.
[0015] Preferably, the mass of the air entraining agent is 0.005-0.01% of the mass of aluminate cement.
[0016] Preferably, the air entraining agent includes at least one of rosin resins, alkyl sulfonic acids, alkyl aromatic sulfonic acids and fatty alcohol sulfonates.
[0017] The present invention also provides a method for preparing the cement adhesive described in the above technical solution, comprising:
[0018] Aluminate cement, artificial porcelain sand, titanium oxide, silica powder, admixture and water are mixed to obtain cement adhesive.
[0019] The present invention also provides the use of the cement adhesive described in the above technical solution or the cement adhesive prepared by the preparation method described in the above technical solution in anti-pollution porcelain insulators in high-cold areas.
[0020] Preferably, the application comprises: pouring cement adhesive into anti-pollution porcelain insulators for high-cold areas, and then sequentially performing steam curing and water curing.
[0021] The invention provides a cement adhesive, comprising the following components: aluminate cement, artificial porcelain sand, titanium oxide, silica micropowder, an admixture and water; the water-cement ratio of the cement adhesive is 0.1-0.2; the admixture comprises an air entraining agent, a water reducer, an antifreeze agent, a reinforcing agent and a steep wave performance improver; the water reducer is a high-efficiency polycarboxylate water reducer; the mass of the reinforcing agent is 0.1-0.3% of the total mass of the aluminate cement, artificial porcelain sand, titanium oxide and silica micropowder. The present invention adds an air entraining agent. In cold regions, the bubbles formed by the air entraining agent can absorb frost heave stress and reduce the degree of damage to the cement adhesive. The bubbles can also prevent water penetration and reduce the formation of pores and cracks. At the same time, during the drying process, the bubbles can also absorb part of the stress when the cement adhesive shrinks, reduce the degree of shrinkage, and reduce the probability of cracks, thereby improving the cold resistance of the cement adhesive. By limiting the range of the water-cement ratio, the amount of water can be controlled to avoid excessive content of freezable water in the cement adhesive, too fast freezing speed, poor bubble structure, and too large average bubble spacing, which reduces the cold resistance. Experimental results show that the cement adhesive provided by the present invention can significantly improve the cold resistance while ensuring working performance and strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is the compressive strength of the cement adhesive prepared in Example 1 and Comparative Examples 1-2;
[0023] Figure 2 is the flexural strength of the cement adhesive prepared in Example 1 and Comparative Examples 1-2;
[0024] Figure 3 is the compressive strength of the cement adhesive prepared in Example 2;
[0025] Figure 4 is the flexural strength of the cement adhesive prepared in Example 2;
[0026] Figure 5 is the compressive strength of Application Example 1 and Comparative Application Example 1;
[0027] Figure 6 is the flexural strength of Application Example 1 and Comparative Application Example 1;
[0028] Figure 7 It is the elastic modulus of the cement adhesive prepared in Examples 4-5 and Comparative Examples 4-5 after 28 days of frost resistance test. DETAILED DESCRIPTION
[0029] The present invention provides a cement adhesive, comprising the following components: aluminate cement, artificial porcelain sand, titanium oxide, silica powder, external admixture and water;
[0030] The water-cement ratio of the cement adhesive is 0.1-0.2;
[0031] The external admixtures include air entraining agent, water reducing agent, antifreeze agent, reinforcing agent and steep wave performance improving agent;
[0032] The water reducer is a high-efficiency polycarboxylate water reducer;
[0033] The mass of the reinforcing agent is 0.1-0.3% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silicon powder.
[0034] The present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.
[0035] In the present invention, the cement binder comprises aluminate cement. In the present invention, the aluminate cement is a matrix material.
[0036] As an implementation mode, the aluminate cement may be CA50-II aluminate cement.
[0037] In the present invention, the cement adhesive further comprises artificial porcelain sand; the particle size of the artificial porcelain sand is preferably 30-80 meshes. In the present invention, the artificial porcelain sand has good wear resistance, corrosion resistance and high temperature resistance, and can effectively improve the fluidity of the cement adhesive.
[0038] In the present invention, the cement binder further comprises titanium oxide; the particle size of the titanium oxide is preferably 20 to 80 nm. In the present invention, the titanium oxide in the cement binder can significantly improve the mechanical properties and cold resistance of the cement binder; the use of nanometer size can accelerate the hydration of cement, reduce the setting time and enhance the mechanical properties.
[0039] In the present invention, the cement binder further comprises silicon micropowder; the particle size of the silicon micropowder is preferably 0.1-0.2 μm; the content of SiO2 in the silicon micropowder is preferably ≥90.0wt%. In the present invention, the silicon micropowder can significantly improve the mechanical properties and cold resistance of the cement binder.
[0040] Taking the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder as 100%, the mass content of aluminate cement is preferably 45-60%; the mass content of artificial porcelain sand is preferably 35-50%; the mass content of titanium oxide is preferably 1-3%; and the mass of silica powder is preferably the remainder. In the present invention, limiting the contents of aluminate cement, artificial porcelain sand, titanium oxide and silica powder within the above range can further improve the cold resistance of cement adhesive.
[0041] As an embodiment, based on the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder as 100%, the mass content of the aluminate cement can be 50-55%; the mass content of the artificial porcelain sand can be 43-45%; the mass content of the titanium oxide can be 2%; and the mass content of the silica powder can be 5%.
[0042] In the present invention, the cement adhesive further includes an admixture; the admixture includes an air entraining agent. In the present invention, in cold regions, the bubbles formed by the air entraining agent can absorb frost heave stress and reduce the degree of damage to the cement adhesive; the bubbles can also prevent water penetration and reduce the formation of pores and cracks; at the same time, during the drying process, the bubbles can also absorb part of the stress when the cement adhesive shrinks, reduce the degree of shrinkage, and reduce the probability of cracks, thereby improving the cold resistance of the cement adhesive.
[0043] In the present invention, the mass of the air entraining agent is preferably 0.005-0.01% of the mass of aluminate cement; the air entraining agent preferably includes at least one of rosin resin, alkyl sulfonic acid, alkyl aromatic sulfonic acid and fatty alcohol sulfonate. In the present invention, limiting the mass of the air entraining agent to the above range can further improve the cold resistance of the cement adhesive.
[0044] As an implementation mode, the mass of the air entraining agent may be 0.006-0.008% of the mass of aluminate cement; the air entraining agent may be AE330 air entraining agent.
[0045] In the present invention, the external admixture further comprises a water reducing agent, an antifreeze agent, a reinforcing agent and a steep wave performance improving agent.
[0046] In the present invention, the water reducer is a high-efficiency polycarboxylate water reducer; the mass of the water reducer is preferably 0.1-0.3% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder. In the present invention, in the preparation process of cement adhesive, the use of high-efficiency polycarboxylate water reducer can significantly improve its performance. This water reducer can effectively reduce the porosity in cement paste, thereby increasing the density of the paste, not only improving the strength of cement adhesive, but also enhancing its compressive strength; by using high-efficiency polycarboxylate water reducer, the overall performance of cement adhesive can be improved while ensuring the construction performance, making it more suitable for various engineering needs.
[0047] In the present invention, the water reducer is preferably a polycarboxylic acid water reducer with acrylic acid / methacrylic acid as the main chain or a polycarboxylic acid water reducer with maleic anhydride as the main chain. The present invention has no particular limitation on the source of the water reducer, and a high-efficiency polycarboxylic acid water reducer well known to those skilled in the art can be used.
[0048] As an implementation mode, the mass of the water reducing agent may be 0.1-0.2% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder.
[0049] In the present invention, the antifreeze agent is preferably an organic alcohol; the mass of the antifreeze agent is preferably 0.1-0.3% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder. In the present invention, the antifreeze agent can improve the antifreeze effect of cement adhesive.
[0050] As an implementation mode, the mass of the antifreeze agent can be 0.2-0.25% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder.
[0051] In the present invention, the reinforcing agent is preferably polypropylene fiber; the diameter of the polypropylene fiber is preferably 0.02-0.04 mm; the length of the polypropylene fiber is preferably 2-3 mm; the mass of the reinforcing agent is 0.1-0.3% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder. In the present invention, the reinforcing agent has the characteristics of high strength and high modulus, and can effectively improve the flexural properties of cement adhesive; at the same time, the reinforcing agent can also prevent the flexural strength from decreasing with the increase of age, thereby ensuring the stability of the cement adhesive at different use stages; by using polypropylene fiber as a reinforcing agent, the cement adhesive can maintain good performance during long-term use and meet various engineering requirements.
[0052] As an implementation mode, the mass of the reinforcing agent may be 0.2-0.25% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder.
[0053] In the present invention, the steep wave performance improver is preferably sodium chloride; the mass of the steep wave performance improver is preferably 0.02-0.05% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder. In the present invention, the steep wave performance improver can improve the steep wave performance of cement adhesive.
[0054] As an implementation mode, the mass of the steep wave performance improver can be 0.03-0.04% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder.
[0055] In the present invention, the cement adhesive further comprises water. In the present invention, the water is a solvent.
[0056] In the present invention, the water-cement ratio of the cement binder is 0.1-0.2, preferably 0.14-0.19, and more preferably 0.15-0.18. In the present invention, by limiting the range of the water-cement ratio, the amount of water can be controlled to avoid excessive freezable water content in the cement binder, too fast freezing speed, poor bubble structure, too large average bubble spacing, and reduced cold resistance.
[0057] The present invention adds an air entraining agent. In cold areas, bubbles formed by the air entraining agent can absorb frost heave stress and reduce the degree of damage to the cement adhesive. The bubbles can also prevent water penetration and reduce the formation of pores and cracks. Meanwhile, during the drying process, the bubbles can also absorb part of the stress when the cement adhesive shrinks, reduce the degree of shrinkage, and reduce the probability of cracks, thereby improving the cold resistance of the cement adhesive. By limiting the range of the water-cement ratio, the amount of water can be controlled to avoid excessive freezable water content in the cement adhesive, too fast freezing speed, poor bubble structure, excessively large average bubble spacing, and reduced cold resistance.
[0058] The present invention also provides a method for preparing the cement adhesive described in the above technical solution, comprising:
[0059] Aluminate cement, artificial porcelain sand, titanium oxide, silica powder, admixture and water are mixed to obtain cement adhesive.
[0060] The present invention has no special limitation on the mixing operation of the aluminate cement, artificial porcelain sand, titanium oxide, silica powder, admixture and water, and the technical scheme for preparing the mixed material well known to those skilled in the art can be adopted.
[0061] The preparation method provided by the invention has simple process and is suitable for industrial production.
[0062] The present invention also provides the use of the cement adhesive described in the above technical solution or the cement adhesive prepared by the preparation method described in the above technical solution in anti-pollution porcelain insulators in high-cold areas.
[0063] In the present invention, the cement adhesive is preferably coated with a buffer layer on the surface of the anti-pollution type porcelain insulator in high-cold areas before application; the material of the buffer layer is preferably asphalt. The present invention has no special limitation on the thickness of the buffer layer, and an operation well known to those skilled in the art is adopted. In the present invention, coating the buffer layer on the surface of the anti-pollution type porcelain insulator in high-cold areas can improve the electrical performance of the cement adhesive.
[0064] In the present invention, the application preferably includes: pouring cement adhesive into the anti-pollution type porcelain insulator for high-cold areas, and then sequentially performing steam curing and water curing.
[0065] The present invention has no special limitation on the operation of pouring the cement adhesive into the anti-pollution porcelain insulator in high-cold areas, and the operation well known to those skilled in the art can be adopted.
[0066] In the present invention, the steam curing temperature is preferably 45-55°C; the steam curing time is preferably 5-6h; the water curing temperature is preferably 20-30°C; the water curing time is preferably 5-6h. The present invention adopts a composite curing mode of sequentially performing steam curing and water curing. In this curing mode, the cement adhesive is first steam cured to quickly reach a certain strength; then water curing is performed to ensure the stability of the cement adhesive during later use. Through this composite curing mode, the decrease in the flexural strength of the cement adhesive in the middle and late stages can be effectively reduced, thereby improving its overall performance.
[0067] As an embodiment, the temperature of the steaming may be 50-55°C; the temperature of the water-curing may be 25-30°C.
[0068] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0069] Example 1
[0070] The components of cement adhesive are: aluminate cement, artificial porcelain sand, titanium oxide, silica powder, admixture and water;
[0071] The external admixtures are air entraining agent, water reducing agent, antifreeze agent, reinforcing agent and steep wave performance improving agent;
[0072] The mass of the aluminate cement is 50% of the total mass of the aluminate cement, artificial porcelain sand, titanium oxide and silica powder, and the model is CA50-Ⅱ aluminate cement;
[0073] The mass of the artificial porcelain sand is 43% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder, and the particle size is 30-80 mesh;
[0074] The mass of the titanium oxide is 2% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder, and the particle size is 20-80 nm;
[0075] The mass of the silicon micropowder is 5% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silicon micropowder; the particle size of the silicon micropowder is 0.1-0.2 μm; the content of SiO2 in the silicon micropowder is 98wt%;
[0076] The mass of the air entraining agent is 0.008% of the mass of the aluminate cement, and the air entraining agent is AE330 air entraining agent;
[0077] The water reducer is XCA-100 polycarboxylic acid high-performance water reducer; the mass of the water reducer is 0.2% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder;
[0078] The antifreeze agent is an organic alcohol, and its mass is 0.1% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder;
[0079] The reinforcing agent is polypropylene fiber, with a diameter of 0.02-0.04 mm, a length of 2.5 mm, and a mass of 0.2% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder;
[0080] The steep wave performance improver is sodium chloride, the mass of which is 0.04% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder;
[0081] The water-cement ratio of the cement binder is 0.13;
[0082] The preparation method of the cement adhesive is:
[0083] Aluminate cement, artificial porcelain sand, titanium oxide, silica powder, admixture and water are mixed to obtain cement adhesive.
[0084] Comparative Example 1
[0085] On the basis of Example 1, titanium oxide was omitted, the mass of artificial porcelain sand was changed to 45% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder, the water-cement ratio was changed to 0.19, and other conditions remained unchanged.
[0086] Comparative Example 2
[0087] On the basis of Example 1, the artificial porcelain sand was changed to river sand, the water-cement ratio was changed to 0.14, and other conditions remained unchanged.
[0088] The cement adhesive prepared in Example 1 and Comparative Examples 1-2 was subjected to performance tests after curing at 25°C for 5 hours. The flexural strength, compressive strength, shrinkage rate and the like were tested in accordance with JB / T 4307-2004 "Cement adhesive for insulator assembly"; the fluidity of the cement adhesive was tested in accordance with GB / T 2419-2005 "Method for determination of fluidity of cement mortar", and the results are shown in Tables 1-2. Figure 1 and Figure 2 As shown; Figure 1 is the compressive strength of the cement adhesive prepared in Example 1 and Comparative Examples 1-2, Figure 2 It is the flexural strength of the cement adhesive prepared in Example 1 and Comparative Examples 1-2.
[0089] Table 1 Performance data of cement adhesives prepared in Example 1 and Comparative Examples 1-2
[0090]
[0091] Table 2 Performance data of cement adhesives prepared in Example 1 and Comparative Examples 1-2
[0092]
[0093] From Table 1~2, Figure 1 and Figure 2 It can be seen that the flexural strength of the cement adhesive of the present invention can be increased by 14.5 MPa, the compressive strength can be increased by 34 MPa, and the problem of decreased flexural strength of the cement adhesive in the middle and late stages can be significantly improved.
[0094] Example 2
[0095] On the basis of Example 1, the mass content of the reinforcing agent was modified to 0.1%, and other conditions remained unchanged.
[0096] According to the test method of Example 1, the performance test of the cement adhesive prepared in Example 2 was carried out after curing in water at 25°C for 5 hours. The results are shown in Table 3. Figure 3 and Figure 4 As shown, Figure 3 is the compressive strength of the cement adhesive prepared in Example 2, Figure 4 It is the flexural strength of the cement adhesive prepared in Example 2.
[0097] Table 3 Performance data of cement adhesive prepared in Example 2
[0098]
[0099] From Table 3, Figure 3 and Figure 4 It can be seen that the present invention can significantly improve the strength of cement adhesive and effectively prevent the flexural strength from decreasing with increasing age.
[0100] Example 3
[0101] On the basis of Example 1, the mass content of the reinforcing agent was modified to 0.3%, and other conditions remained unchanged.
[0102] Application Example 1
[0103] The cement adhesive prepared in Example 3 was poured into the anti-pollution porcelain insulator for high-cold areas, and then steam-cured at 48° C. for 3 h and water-cured at 25° C. for 3 h.
[0104] Comparative Example 3
[0105] On the basis of Example 3, the type of water reducer was changed to naphthalene-based water reducer, model SBTJM®-B naphthalene-based high-efficiency water reducer, and other conditions remained unchanged.
[0106] Comparative application example 1
[0107] The cement adhesive prepared in Comparative Example 3 was poured into the anti-pollution porcelain insulator for high-cold areas, and then steam-cured at 48° C. for 3 hours and water-cured at 25° C. for 3 hours.
[0108] According to the test method of Example 1, performance tests were performed on Example 1 and Comparative Application Example 1. The results are shown in Tables 4-5. Figure 5 and Figure 6 As shown, Figure 5 is the compressive strength of Application Example 1 and Comparative Application Example 1, Figure 6 It is the flexural strength of Application Example 1 and Comparative Application Example 1.
[0109] Table 4 Performance data of application example 1 and comparative application example 1
[0110]
[0111] Table 5 Performance data of application example 1 and comparative application example 1
[0112]
[0113] From Table 4~5, Figure 5 and Figure 6 It can be seen that the use of high-efficiency polycarboxylate water-reducing agent can greatly improve the mechanical properties of cement adhesive, with the compressive strength increased by up to 44.4MPa and the flexural strength increased by up to 11.5MPa.
[0114] Comparative Example 4
[0115] Based on Example 1, the air entraining agent was omitted, and the water-cement ratio was changed to 0.2, while other conditions remained unchanged.
[0116] Example 4
[0117] Based on Example 1, the water-cement ratio was modified to 0.2, and other conditions remained unchanged.
[0118] Comparative Example 5
[0119] Based on Example 1, the air entraining agent was omitted, and the water-cement ratio was changed to 0.15, while other conditions remained unchanged.
[0120] Example 5
[0121] Based on Example 1, the water-cement ratio was modified to 0.15, and other conditions remained unchanged.
[0122] The cement adhesives prepared in Examples 1 to 5 and Comparative Examples 4 to 5 were subjected to a performance test after curing in water at 25°C for 6 hours. The antifreeze performance of the cement adhesive was tested according to the national standard "Test Method for Antifreeze Performance of Cement Mortar" (GB / T 41060-2021). After the antifreeze performance test, the antifreeze performance data of the cement adhesives prepared in Examples 1 to 3 after curing are shown in Table 6. The elastic modulus of the cement adhesives prepared in Examples 4 to 5 and Comparative Examples 4 to 5 after curing for 28 days is shown in Table 6. Figure 7 shown.
[0123] Table 6 Antifreeze performance data of the cement adhesive prepared in Examples 1 to 3 after curing
[0124]
[0125] It can be seen from Table 6 that the cement adhesive provided by the present invention has excellent antifreeze performance.
[0126] from Figure 7 It can be seen that by adjusting the water-cement ratio and the amount of air-entraining agent, the cold resistance of the cement adhesive can be significantly improved while ensuring its working performance and strength.
[0127] Example 6
[0128] The components of cement adhesive are: aluminate cement, artificial porcelain sand, titanium oxide, silica powder, admixture and water;
[0129] The external admixtures are air entraining agent, water reducing agent, antifreeze agent, reinforcing agent and steep wave performance improving agent;
[0130] The mass of the aluminate cement is 60% of the total mass of the aluminate cement, artificial porcelain sand, titanium oxide and silica powder, and the model is CA50-II aluminate cement;
[0131] The mass of the artificial porcelain sand is 35% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder, and the particle size is 30-80 mesh;
[0132] The mass of the titanium oxide is 1% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder, and the particle size is 20-80 nm;
[0133] The mass of the silicon micropowder is 4% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silicon micropowder; the particle size of the silicon micropowder is 0.1-0.2 μm; the content of SiO2 in the silicon micropowder is 98wt%;
[0134] The mass of the air entraining agent is 0.01% of the mass of aluminate cement, and the air entraining agent is AE330 air entraining agent;
[0135] The water reducer is XCA-100 polycarboxylic acid high-performance water reducer; the mass of the water reducer is 0.3% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder;
[0136] The antifreeze agent is an organic alcohol, and its mass is 0.2% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder;
[0137] The reinforcing agent is polypropylene fiber, with a diameter of 0.02-0.04 mm, a length of 2.5 mm, and a mass of 0.1% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder;
[0138] The steep wave performance improver is sodium chloride, the mass of which is 0.02% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder;
[0139] The water-cement ratio of the cement binder is 0.13;
[0140] The preparation method of the cement adhesive is:
[0141] Aluminate cement, artificial porcelain sand, titanium oxide, silica powder, admixture and water are mixed to obtain cement adhesive.
[0142] Example 7
[0143] The components of cement adhesive are: aluminate cement, artificial porcelain sand, titanium oxide, silica powder, admixture and water;
[0144] The external admixtures are air entraining agent, water reducing agent, antifreeze agent, reinforcing agent and steep wave performance improving agent;
[0145] The mass of the aluminate cement is 45% of the total mass of the aluminate cement, artificial porcelain sand, titanium oxide and silica powder, and the model is CA50-II aluminate cement;
[0146] The mass of the artificial porcelain sand is 50% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder, and the particle size is 30-80 mesh;
[0147] The mass of the titanium oxide is 3% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder, and the particle size is 20-80 nm;
[0148] The mass of the silicon micropowder is 2% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silicon micropowder; the particle size of the silicon micropowder is 0.1-0.2 μm; the content of SiO2 in the silicon micropowder is 98wt%;
[0149] The mass of the air entraining agent is 0.005% of the mass of the aluminate cement, and the air entraining agent is AE330 air entraining agent;
[0150] The water reducer is XCA-100 polycarboxylic acid high-performance water reducer; the mass of the water reducer is 0.1% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder;
[0151] The antifreeze agent is an organic alcohol, and its mass is 0.3% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder;
[0152] The reinforcing agent is polypropylene fiber, with a diameter of 0.02-0.04 mm, a length of 2.5 mm, and a mass of 0.3% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder;
[0153] The steep wave performance improver is sodium chloride, the mass of which is 0.05% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder;
[0154] The water-cement ratio of the cement binder is 0.13;
[0155] The preparation method of the cement adhesive is:
[0156] Aluminate cement, artificial porcelain sand, titanium oxide, silica powder, admixture and water are mixed to obtain cement adhesive.
[0157] The cement adhesives prepared in Examples 6-7 were subjected to performance tests according to the test method of Example 1 after being cured in water at 25°C for 5 hours. The results are shown in Tables 7-8.
[0158] Table 7 Performance data of cement adhesives prepared in Examples 6 to 7
[0159]
[0160] Table 8 Performance data of cement adhesives prepared in Examples 6-7
[0161]
[0162] It can be seen from Tables 7-8 that the cement adhesive of the present invention has excellent mechanical strength.
[0163] The cement adhesive prepared in Examples 6 to 7 was cured in water at 25°C for 6 hours, and then the antifreeze performance of the cement adhesive was tested according to the national standard "Test Method for Antifreeze Performance of Cement Mortar" (GB / T 41060-2021). After the antifreeze test, the antifreeze performance data of the cement adhesive prepared in Examples 6 to 7 after curing are shown in Table 9.
[0164] Table 9 Antifreeze performance data of cement adhesive prepared in Examples 6-7 after curing
[0165]
[0166] It can be seen from Table 9 that the cement adhesive provided by the present invention has excellent antifreeze performance.
[0167] It can be seen from the above embodiments and comparative examples that the cement adhesive provided by the present invention can improve cold resistance.
[0168] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A cement adhesive, characterized in that: It is composed of the following components: aluminate cement, artificial porcelain sand, titanium oxide, silica powder, admixture and water; The water-cement ratio of the cement adhesive is 0.1-0.2; The external admixtures are air entraining agent, water reducing agent, antifreeze agent, reinforcing agent and steep wave performance improving agent; The water reducer is a high-efficiency polycarboxylate water reducer; The mass of the reinforcing agent is 0.1-0.3% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder; The mass of the air entraining agent is 0.005-0.01% of the mass of the aluminate cement; The mass of the titanium oxide is 1-3% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder; The steep wave performance improving agent is sodium chloride.
2. The cement adhesive according to claim 1, characterized in that: The mass of the aluminate cement is 45-60% of the total mass of the aluminate cement, artificial porcelain sand, titanium oxide and silica powder.
3. The cement adhesive according to claim 1, characterized in that: The mass of the artificial porcelain sand is 35-50% of the total mass of aluminate cement, artificial porcelain sand, titanium oxide and silica powder.
4. The cement adhesive according to claim 1, characterized in that: The particle size of the titanium oxide is 20-80 nm.
5. The cement adhesive according to claim 1, characterized in that: The air entraining agent includes at least one of rosin resins, alkyl sulfonic acids, alkyl aromatic sulfonic acids and fatty alcohol sulfonates.
6. The method for preparing the cement adhesive according to any one of claims 1 to 5, characterized in that: include: Aluminate cement, artificial porcelain sand, titanium oxide, silica powder, admixture and water are mixed to obtain cement adhesive.
7. Use of the cement adhesive according to any one of claims 1 to 5 or the cement adhesive prepared by the preparation method according to claim 6 in anti-pollution porcelain insulators in high-cold areas.
8. The use according to claim 7, characterized in that: The application comprises: pouring cement adhesive into anti-pollution porcelain insulators in high-cold areas, and then sequentially performing steam curing and water curing.
Citation Information
Patent Citations
Extremely cold type cement adhesive
CN107500651A
Cement adhesive as well as preparation method and application thereof
CN116425479A
Cement adhesive for quickly testing strength of porcelain insulator porcelain piece as well as preparation method and application of cement adhesive
CN117756484A